PEMBERDAYAAN KELOMPOK WANITA DALAM PENGOLAHAN LIMBAH (BY PRODUCT) UNGGAS MENJADI PRODUK PANGAN HEWANI BERKUALITAS UNTUK MENINGKATKAN PENDAPATAN DI DESA ALU KECAMATAN ALU - Haloho, Ruth Dameria; Irmayanti, Irmayanti; Minanga, Yunus Tandi; Urfani, Yulinda (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2025)
Chicken is one of the most widely raised and cultivated poultry for human use. The most widely raised types of chicken are llayers and broilers. Alu Village, located in A District in Polewali Mandar District, has a large population of farmers and livestock breeders. The population of chicken farms is quite large in this area and produces quite a lot of chicken farm waste. This is what makes it necessary to carry out the tridharma of higher education, namely community service by conducting training to make chicken feet and intestine chips in order to provide new knowledge and skills in processing poultry waste for the Bocco Tallu women's farmer group. The methods used consist of: providing material on the benefits and nutritional content of intestines and feet, demonstrations of making intestines and feet. The results of the implementation of community service in processing poultry waste and feet are that 95% of participants understand the making of intestines and feet chips, participants are able to understand and know how to make intestine and feet chips as well as poultry waste processing technology and packaging poultry waste products, participants are interested in starting a chicken feet sales business, participants are able to calculate the profit from chicken feet sales by 90%. Based on the results of the business analysis, the income that can be obtained from the sale of chicken feet and intestine chips is IDR 35,000 / kg. This community service needs to be improved further so that it is able to produce large-scale intestine and chicken feet chips so that it can open up employment opportunities and absorb workers.